2012
DOI: 10.18785/gcr.2401.04
|View full text |Cite
|
Sign up to set email alerts
|

Early Growth of Three Kingfish (Menticirrhus) Species Found in Coastal Waters of the Northern Gulf of Mexico

Abstract: Southern kingfish (Menticirrhus americanus), gulf kingfish (M. littoralis), and northern kingfish (M. saxatilis) are members of the drum family (Sciaenidae) that are widespread in coastal habitats of the western Atlantic, including in the Gulf of Mexico (GOM). Despite their economic and ecological importance, little is known about growth of young kingfish. Young kingfish were collected from four different Mississippi shoreline habitats in 2005 and 2006; two associated with barrier islands and two along the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Additionally, there were fi sh in the spawning-capable phase in both March and October, although no females were in the actively spawning subphase during these months. Our estimate of the Southern Kingfi sh spawning period is supported by Anderson et al (2012), who studied daily growth rings in otoliths from juveniles in the northcentral GOM and estimated birth dates with back calculation. Although there were fi sh in that study with (2013) did not directly report RBF data for Southern Kingfi sh from Georgia, but we calculated RBF to be 308.6 eggs g −1 total weight (SE 27.6) on the basis of information in their manuscript.…”
Section: Discussionsupporting
confidence: 67%
“…Additionally, there were fi sh in the spawning-capable phase in both March and October, although no females were in the actively spawning subphase during these months. Our estimate of the Southern Kingfi sh spawning period is supported by Anderson et al (2012), who studied daily growth rings in otoliths from juveniles in the northcentral GOM and estimated birth dates with back calculation. Although there were fi sh in that study with (2013) did not directly report RBF data for Southern Kingfi sh from Georgia, but we calculated RBF to be 308.6 eggs g −1 total weight (SE 27.6) on the basis of information in their manuscript.…”
Section: Discussionsupporting
confidence: 67%
“…Also, the MSF was higher for specimens collected from marsh edges than sandy shorelines during both years, especially during 2005. Anderson et al (2012) found that M. americanus collected in 2005 from marsh edges grew significantly faster than M. americanus collected along sandy shorelines. Foraging success was likely higher for M. americanus at marsh edges in 2005.…”
Section: Discussionmentioning
confidence: 87%
“…However, we examined more stomachs from M. americanus (79) than from M. littoralis (49) or M. saxatilis (33). Furthermore, most M. americanus specimens were collected from inshore habitats, where species richness from seine collections was higher than at surf zones (Anderson, 2009). McMichael and Ross (1987) also reported M. americanus had a more diverse diet than the other kingfish species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations